Analysis of satellite-terrestrial frequency sharing technology for 5G and 6G mobile communication - HU Yanwei; GONG Jian; MA Zhanshu (Dianxin kexue)
In recent years, mobile communication technology has developed rapidly, with 5G networks being widely deployed globally, and research on 6G technology is also underway. With the rapid economic development and increased investment in satellite-based facilities, China's satellite communication, satellite navigation and other satellite application industries are expected to enter a period of rapid development, and the trend of building a satellite-terrestrial integrated network will become the future direction of communication development. The demand for frequency resources in satellite communication overlaps with that of ground mobile communication systems, and the problems of co-frequency interference and strong power suppression interference between mobile communication and satellite communication are becoming increasingly prominent. The frequency sharing technology for 5G and 6G mobile communication satellite-terrestrial integration was analyzed from the perspectives of technology research, policy formulation, and station layout, providing reference for building a satellite-terrestrial integrated global seamless communication system.